Synthesis of Carbon Nanotubes and Nanobelts on Thin Iron Film by Thermal Chemical Vapor Deposition Method - Udomdej Pakdee; Noppadon Suttisiri; Ekachai Hoonnivathana; Surasak Chiangga (Agriculture and Natural Resources, 2007)
The carbon nanotubes (CNTs) were synthesized from acetylene gas (C2H2) by thermal chemical vapor deposition method for the formation of catalytic iron nanoparticles was used Hydrogen (H2) as the environment gas. The CNTs were synthesized on iron nanoparticles as catalyst and on the wall of stainless steel chamber. The size of carbon nanobelts was about 300 nm (wide).